Analisis Leksikografi dan Semantik Perkataan al-Kafur dalam Al-Qur’an (Analysis of Lexicography and Semantic The word al-Kafur in the Quran) - Ramli, Saipolbarin; Atoh, Nazri; Mohd Zakaria, Zarima; Mohammad Som, Hairullfazli; Abd Rahman, Mohd Zaki (Universiti Kebangsaan Malaysia Press, 2018)
The word al-Kafur is one of terms used for plants in the Quran. Al-Kafur is only cited once in the Quran, which is in the fifth verse of al-Insan. Discussions of the word al-Kafur in Arabic language can be found in the fields of Arabic philology, hadith, Quranic interpretation, lexicography and Arabic poetry. There were disagreements among Arab-Islamic scholars in determining the meaning of word al-Kafur. Some of them refer to it as cinnamomum camphora, some refer to it as the oleander tree, while others gave it other meanings. The factor that led to the dispute among Arab-Islamic scholars was due to the fact that word al-Kafur in the Quran carries the meaning of blessings in heaven. This study aims to elucidate the meaning of the word al-Kafur as described in the Quran. The study adopted a qualitative approach, which used the library search method in data collection and analysis. In an effort to achieve substantial data, the discussion involved the use of the world al-Kafur in different context as used in the interpretations of Quran, hadiths and Arabic poetry. This study also used comparative data from the fields of agricultural science and Islamic medical sciences. Finding from this study showed that the closest interpretation of the world al-Kafur as described in the Quran is cinnamomum camphora. This study has dissolved the conflict in understanding the Quranic verse and rejects allegations of imperfections in the content of the Quran.